Evaluation Of Drug Use In Patients With Hypertension Antihypertensive With Complications Diabetes Melitus And Chronic Kidney Disease In "X" Hospital 2014 - Sari, Desy Nurmalita; , Zakky Cholisoh, Ph.D.,Apt (2016)
dIn Indonesia, the number of hypertensive patients reached 32 percent in 2008 around the age of 25 years. The condition increases in blood pressure that is not handled properly will cause complications, including chronic renal failure and diabetes mellitus. The purpose of this study was to evaluate the rationality of the use of antihypertensive drugs in hypertensive patients with chronic renal complications of kidney failure and diabetes mellitus based on precise indications, right patient, right drug, right patient and. This type of research is non-experimental. Collecting data in this study using a retrospective method by looking at the patient medical record. Number of research subjects in this study were 43 patients who met the inclusion criteria. References used in the evaluation of rationality appropriate indications and appropriate patient was The Seventh Joint National Committee in 2003 and Pharmacotherapy A pathophysiologic Approach in 2008, while the right dosage and proper evaluation of patients using the British National Formulary 57 in 2009 and Drug Dosing Renal Failure 2000. Evaluation of the use of antihypertensive drugs in hypertensive patients with complications in hospitals Surakarta in 2014, draw the following conclusion, use of antihypertensive drugs in this study is 46.51%, 41.86% irbesartan, 39.53% of intravenous furosemide, bisoprolol 28.93 %, oral furosemide 27.90%, 25.58% captopril, lisinopril 18.60%, verapamil 4.65%, 2.32% spironolactone. The evaluation results on the use of antihypertensive drugs in hypertensive patients with complications of diabetes mellitus and chronic renal failure in 43 subjects of research, namely, 100% precise indication, a 100% right patient, right drug 79.07%, and 83.73% correct dose.